Rancang Bangun Aplikasi Peramalan Permintaan Barang Dengan Metode Double Exponential Smoothing Pada CV Multi Usaha Mandiri Surabaya - Huda, Nanang Misbachul; Rahmawati, Endra; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
CV Multi Usaha Mandiri is a distributor of food and beverage packaging that serve in Surabaya, Sidoarjo and Gresik. CV. Multi Usaha Mandiri is currently experience of want or out of stock. Based on the facts of the CV Multi Usaha Mandiri admin at this time the requests from the sales department fluctuate the amount of preparation must be prepared by CV Multi Usaha Mandiri becomes unstable and often occur. Requests from the customers are unfullfilled. To be able to solve the problems that occur, made an application to perform activities that can predict the work of demands for the future. Forecasting used is the method of forecasting Double Exponential Smoothing. The result of the data pattern test showing that the data have a seasional tendency and exponential smoothing methods - Brown has average forecasting errors (236,070.45) compared to other methods. This method requires data as input, demand data is processed from sales data to generate a forecast that can help determine the amount of preparation in the two periods to come. This application can generate forecasting values by considering the value of α constants (0.1) and generating reports of goods to be ordered. So the company can find out the information needed, especially about the fulfillment of inventory